Estrategias metodológicas y su incidencia en la comprensión lectora en el proceso de enseñanza-aprendizaje de los estudiantes del tercero bachillerato agropecuario en la unidad educativa “José Rodríguez Labandera” periodo lectivo 2021-2022 - Quila Rizzo, Oswal Manrrique (2022)
The project was born from the difficulties observed in reading comprehension in students of the Third Agricultural Baccalaureate due to the lack of application of methodological strategies to improve reading comprehension in the teaching-learning process. The objective of this study is: to implement methodological strategies that allow improving reading comprehension in the teaching-learning process of Third Agricultural Baccalaureate students through training for teachers of the "José Rodríguez Labandera" Educational Unit. In the development of the research qualitative and quantitative methods were used propositional type with non-experimental design, a field work, the research is an exploratory type work, the inductive-deductive method is used for the inquiry process; The explanatory research has allowed to determine the cause and effect of the problem posed and through the theoretical framework to search for alternative solutions that contribute to improving the learning process of the students. The results obtained reveal that a large group of students have deficiencies in reading comprehension related to not taking punctuation marks into account, difficulties in writing a report, the lack of connectors when writing, which affects a low level of academic performance To contribute To solve the problem, a training plan is proposed for teachers in the agricultural area. Training plan that has been evaluated to determine the strengthening of reading comprehension in the teaching-learning process in the students of the Third Agricultural Baccalaureate of the José Rodríguez Labandera Educational Unit